In silico analysis of mutations near S1/S2 cleavage site in SARS‐CoV‐2 spike protein reveals increased propensity of glycosylation in Omicron strain. Issue 9 (7th June 2022) - Beaudoin, Christopher A.; Pandurangan, Arun P.; Kim, So Yeon; Hamaia, Samir W.; Huang, Christopher L.‐H.; Blundell, Tom L.; Vedithi, Sundeep Chaitanya; Jackson, Antony P.
Abstract: Cleavage of the severe respiratory syndrome coronavirus‐2 (SARS‐CoV‐2) spike protein has been demonstrated to contribute to viral‐cell fusion and syncytia formation. Studies have shown that variants of concern (VOC) and variants of interest (VOI) show differing membrane fusion capacity. Mutations near cleavage motifs, such as the S1/S2 and S2' sites, may alter interactions with host proteases and, thus, the potential for fusion. The biochemical basis for the differences in interactions with host proteases for the VOC/VOI spike proteins has not yet been explored. Using sequence and structure‐based bioinformatics, mutations near the VOC/VOI spike protein cleavage sites were inspected for their structural effects. All mutations found at the S1/S2 sites were predicted to increase affinity to the furin protease but not TMPRSS2. Mutations at the spike residue P681 in several strains, such P681R in the Delta strain, resulted in the disruption of a proline‐directed kinase phosphorylation motif at the S1/S2 site, which may lessen the impact of phosphorylation for these variants. However, the unique N679K mutation in the Omicron strain was found to increase the propensity for O‐linked glycosylation at the S1/S2 cleavage site, which may prevent recognition by proteases. Such glycosylation in the Omicron strain may hinder entry at the cell surface and, thus, decrease syncytia formation and induce cell entry through the endocytic pathway as has been shown in previous studies. Further experimental work is needed to confirm the effect of mutations and posttranslational modifications on SARS‐CoV‐2 spike protein cleavage sites.